(untitled) (Eurasian Medical Research Periodical, 2023)
The purpose of the study. Assessment of the effectiveness of the nursing approach in bronchial asthma by training and self - monitoring of patients to develop the qualifications and medical level of nurses according to the nursing approach algorithm for patients with bronchial asthma.